The Effect of Truth or Dare Game on Students’ Speaking Achievement at SMP Negeri 9 Kendari - Priskilla, Christhine; Siam, Siam (Journal of Teaching of English, 2021)
This study is conducted to examine the effect of Truth or Dare Game on Students’ Speaking Achievement at SMP Negeri 9 Kendari. This research was conducted in quasi experimental research design that consist of experimental class and control class. The population of this research wasthe second-grade students of SMP Negeri 9 Kendari which consists of ten classes with the total of the students are 352 students, while the subject of this research wasClass VIII-6 (experimental class) which consists of 36 students and Class VIII-7 (control class) which consists of 36 students. The data of this research was collected by giving pre-test and post-test to students in the form of oral test that related to the topic of asking and giving opinion, expression of like and dislike, and asking and giving personal information. The data was analyzed by using SPSS 16.0 version by using (descriptive analysis and inferential statistics). Descriptive analysis was used to describe the maximum scores, minimum scores, mean score and standard deviation while the inferential statistic was used to examine the hypothesis. As for testing the hypothesis. The result showed that there was an improvement of the students’ speaking achievement. Independent samples ttest suggested that, there was a significant difference in the scores for experimental class ( M = 62.22, SD = 8.81) and control class ( M = 45.00, SD = 7.55), t (70) = 68.400, p (0.000) < 0.05. Therefore, it can be concluded that the value of Sig (2 tailed) is lower than the significance α value (0.000 < 0.05). In other words, alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It means that Truth or Dare game can enrich students’ speaking achievement for Junior High School Student.